Quantification of total phenolic contents and their antioxidant scavenging capacity in selected herbs extract - Haron, Normah; Muhamad Bunnori, Noraslinda; Md Zin, Noor Hasniza; Abdul Wahab, Widya; Abd Halim, Khairul Bariyyah; Mat Jusoh, Hanapi (2016)
Medicinal plants are commonly used in complementary and alternative medicine to treat several chronic diseases. Gynura procumbens, Hibiscus sabdariffa and Clinacanthus nutans are believed to contain high level of antioxidants including phenolic acids that may contribute to antioxidant activities. Thus, the objectives of this study were to determine total phenolic content (TPC) and antioxidant scavenging capacity of these plants using three different extracts as well as to determine the relationship between TPC and antioxidant activity. The quantification of phenolic compound was conducted by analyzing the compounds at three different fractions (free, insoluble bound and soluble bound). Three replicates of the medicinal plants were extracted with 80% methanol (free fraction) and undergone hydrolysis with HCl (soluble bound) and NaOH (insoluble bound). The TPC was determined using Folin-Ciocalteau reagent while antioxidant radical scavenging capacities were analyzed using DPPH assay. Results showed that G. procumbens and C. nutans of the insoluble bound extracts had the highest amount of TPC compared to the free phenolic and soluble bound (p<0.05). Meanwhile, H. sabdariffa had the highest TPC value in soluble bound extract (7.63 + 0.28 mg GAE/g) compared to the free phenolic and insoluble bound extracts (2.78 + 0.20 mg GAE/g and 3.61 + 0.85 mg GAE/g, respectively) (p<0.05). The antioxidant scavenging capacity of the G. procumbens and C. nutans extracts as determined by IC50 values was the highest in the insoluble bound extract followed by free phenolic and soluble bound extracts (p<0.05). In contrast, the soluble bound extract of H. sabdariffa showed the highest IC50 value followed by free phenolic and insoluble bound extracts. We also found strong correlations between TPC with antioxidant radical scavenging capacity. In conclusion, this finding suggests that these plants possess a good source of natural antioxidants, which could be used as an non-conventional substances in the management of inflammatory-related diseases.